MTA2 silencing attenuates the metastatic potential of cervical cancer cells by inhibiting AP1-mediated MMP12 expression via the ASK1/MEK3/p38/YB1 axis - Chia-Liang Lin; Tsung-Ho Ying; Shun-Fa Yang; Hui-Ling Chiou; Yong-Syuan Chen; Shao-Hsuan Kao; Yi-Hsien Hsieh (Cell Death and Disease, 2021)
Abstract Metastasis-associated protein 2 (MTA2) is a transcription factor that is highly associated with matrix metalloproteinase 12 (MMP12). Thus, we hypothesized that MTA2 may regulate MMP12 expression and is involved in cervical cancer metastasis. Results showed that MTA2 and MMP12 were highly expressed in cervical cancer cells, and MTA2 knockdown reduced MMP12 expression and inhibited the metastasis of cervical cancer cells in xenograft mice. MMP12 knockdown did not influence the viability of cervical cancer cells but clearly inhibited cell migration and invasion both in vitro and in vivo. MMP12 was highly expressed in cervical tumor tissues and correlated with the poor survival rate of patients with cervical cancer. Further investigations revealed that p38 mitogen-activated protein kinase (p38), mitogen-activated protein kinase kinase 3 (MEK3), and apoptosis signal-regulating kinase 1 (ASK1) were involved in MMP12 downregulation in response to MTA2 knockdown. Results also demonstrated that p38-mediated Y-box binding protein1 (YB1) phosphorylation disrupted the binding of AP1 (c-Fos/c-Jun) to the MMP12 promoter, thereby inhibiting MMP12 expression and the metastatic potential of cervical cancer cells. Collectively, targeting both MTA2 and MMP12 may be a promising strategy for the treatment of cervical cancer.